Perilaku Cuci Tangan Pakai Sabun pada Santri di Pondok Pesantren Kota Medan - Purnama, Tri Bayu; Eliandy, Sri Rezeki Hartati; Lestari, Cindy (Jurnal Promosi Kesehatan Indonesia, 2020)
Background: Islamic Boarding School is one of the domains of education to introduce the PHBS Program. One of the indicators is washing hands with soap. It is expected that the pesantren community could apply the indicators of PHBS Program and protected from various diseases. This study aimed to describe the practice of washing hands with soap among santri at Islamic Boarding Schools In Medan. Method: This research was a quantitative study using Cross-Sectional design. The sampling technique was using Simple Random Sampling. The population was all students in seven Islamic boarding school in Medan. The samples were 436 santri (students). Data was collected using a questionnaire and analyzed using the Chi-Square test. Result:  The age of students who washed their hands with soap had an insignificant difference in proportions, in which the p-value was 0.204 > 0.005 with Prevalens Risk (PR) on 95% CI 1.331 (0.855 – 2.071). The sex of students who washed their hands with soap had a p-value of 0.137 > 0.005 with PR on 95% CI 0.725 (0.475 – 1.108), which means there was no significant difference in the proportion. The education level also did not have a significant difference with the behavior of washing hands with soap with a p-value of 0.210 > 0.005 with PR on 95% CI 1.375 (0.835 – 2.266). The practice of washing hands with soap among santri was poor. The highest percentage of washing hands with soap among santri was in the boarding school with a percentage of 47.9%. There was no significant difference in the proportion of age, sex, and education level with the practice of handwashing with soap among santri.